When Common Identities Decrease Trust: An Experimental Study of Partisan Women. Issue 3 (6th June 2018) - Klar, Samara
Abstract: How does sharing a common gender identity affect the relationship between Democratic and Republican women? Social psychological work suggests that common ingroup identities unite competing factions. After closely examining the conditions upon which the common ingroup identity model depends, I argue that opposing partisans who share the superordinate identity of being a woman will not reduce their intergroup biases. Instead, I predict that raising the salience of their gender will increase cross‐party biases. I support my hypotheses with a nationally representative survey of 3, 000 adult women and two survey experiments, each with over 1, 000 adult women. These findings have direct implications for how women evaluate one another in contentious political settings and, more broadly, for our understanding of when we can and cannot rely upon common identities to bridge the partisan divide.